1991
DOI: 10.1093/rheumatology/30.1.16
|View full text |Cite
|
Sign up to set email alerts
|

SEROLOGICAL EVIDENCE OF INFECTION WITH HELICOBACTER PYLORI MAY PREDICT GASTROINTESTINAL INTOLERANCE TO NON-STEROIDAL ANTI-INFLAMMATORY DRUG (NSAID) TREATMENT IN RHEUMATOID ARTHRITIS

Abstract: Specific circulating antibodies to the spiral gastric organism, Helicobacter pylori (HP) were detectable in 43% of 68 patients with rheumatoid arthritis by complement fixation test (CFT) and enzyme-linked immunosorbent assay (ELISA), a frequency comparable with that of a normal, age-matched population. Presence of these antibodies correlated strongly with a previous history of peptic ulcer disease (PUD) and to the severity of NSAID-related dyspeptic symptoms, the latter often leading to multiple drug intoleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Endoscopic evidence is flawed in patients undergoing endoscopy for clinical reasons since H. pylori infection is associated with NSAID‐induced dyspepsia, 20 , 25 , 32 –34 making it likely that H. pylori positive individuals would be endoscoped more readily than H. pylori negative individuals 25 and increasing the chances that an incidental ulcer would be discovered by chance. In large studies where patients taking NSAIDs (without ulcer prophylaxis) were endoscoped involuntarily to a set protocol, the incidence of ulceration was almost exactly the same in those who were H. pylori positive or negative 35 .…”
Section: Nsaid and H Pylori—the Endoscopic Evidencementioning
confidence: 99%
“…Endoscopic evidence is flawed in patients undergoing endoscopy for clinical reasons since H. pylori infection is associated with NSAID‐induced dyspepsia, 20 , 25 , 32 –34 making it likely that H. pylori positive individuals would be endoscoped more readily than H. pylori negative individuals 25 and increasing the chances that an incidental ulcer would be discovered by chance. In large studies where patients taking NSAIDs (without ulcer prophylaxis) were endoscoped involuntarily to a set protocol, the incidence of ulceration was almost exactly the same in those who were H. pylori positive or negative 35 .…”
Section: Nsaid and H Pylori—the Endoscopic Evidencementioning
confidence: 99%
“…These results could imply that the presence of H. pylori in NERD prevents the development of gastric mucosal erosion, as shown in ERD through its acid regulation [ 28 ]. In addition, reflux symptoms observed in NERD patients could overlap with other diseases such as IBD and heartburn related to H. pylori infection [ 29 , 30 ]. Our study results also suggested evaluating H. pylori infection in patients with reflux symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they found that H. pylori seropositive RA patients who also had a positive cytotoxinassociated gene A protein (CagA) also scored significantly higher on disease activity score 28 (DAS28) and visual analogue scale (VAS) than their CagA negative counterparts [23]. Jones et al estimated the presence of H. pylori infection to be 43-68% among RA patients, [24] which is consistent with the findings of the study performed by Ebrahimi et al [23]. Zentilin et al confirmed the results of the aforementioned study on the higher rate of ESR and CRP in RA patients with H. pylori infection in comparison to those who are not infected by H. pylori [25].…”
Section: Funding_______________________________mentioning
confidence: 99%